1985
DOI: 10.1530/jrf.0.0740497
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of sperm transport through the rat epididymis after castration

Abstract: Transport of spermatozoa through different regions of the epididymis has been followed by labelling testicular spermatozoa with [3H]thymidine in intact rats and in rats in which the efferent ducts were ligated or the testes were removed. In intact rats, the transit times of epididymal spermatozoa from the initial segment to the caput, from the caput to the corpus, and from the corpus to the cauda were 2, 4 and 2 days, respectively, giving a total transit time of 8 days. After bilateral castration, labelled spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0
2

Year Published

1988
1988
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 16 publications
3
15
0
2
Order By: Relevance
“…There was a one-week lag in the chronological peak in the frequency of morphologically abnormal spermatozoa between caput and cauda epididymis. This phenomenon seems in agreement with the report of Sujarit and Pholpramool (1985), in which they have indicated 8 days for the transportation of spermatozoa from caput to cauda epididymis. In this sense, decreased morphologically abnormal spermatozoa in caput epididymis in Week 4 suggests the likelihood of recovery in the frequency of morphologically abnormal spermatozoa in cauda epididymis in Week 5 and later.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…There was a one-week lag in the chronological peak in the frequency of morphologically abnormal spermatozoa between caput and cauda epididymis. This phenomenon seems in agreement with the report of Sujarit and Pholpramool (1985), in which they have indicated 8 days for the transportation of spermatozoa from caput to cauda epididymis. In this sense, decreased morphologically abnormal spermatozoa in caput epididymis in Week 4 suggests the likelihood of recovery in the frequency of morphologically abnormal spermatozoa in cauda epididymis in Week 5 and later.…”
Section: Discussionsupporting
confidence: 93%
“…In this figure, total transit time of spermatozoa from the initial caput segment to vas deferens was set at 11 days. Breakdown of the time is as follows: 8 days for the transit of epididymal spermatozoa from the initial caput segment to the caudal epididymis in rats (Sujarit and Pholpramool, 1985), and 3 days for caudal spermatozoa to move into the vas deferens (adopted from the data in mice, Sega and Owens, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, morphologically abnormal spermatozoa increased from Week 3 and the increased values lasted until Week 5. The presumable exposure periods of germ cells in these recovery periods were stages from the leptotene to mid spermatid in the current study (total transit time for spermatozoa from the initial caput segment to cauda epididymis was considered to be 8 days [12]) which was completely consistent with the UDS observed in mice. Furthermore, peak severity in the frequency of morphologically abnormal spermatozoa was observed in Week 4, in which germ cells were assumed to be exposed to MMS d urin g the pe riod of late pachy ten e spermatocytes and early spermatids.…”
Section: Discussionsupporting
confidence: 84%
“…Although this study used a lower dose of DES compared with that in the above-cited study, we speculate that DES has the effect of retarding epididymis development. In addition, a study reported that decreased testosterone concentrations speed up the passage of sperms through the epididymis (Sujarit and Pholpramool, 1985); therefore, the epididymis weight decrease may have been influenced not only by the direct action of DES on the epididymis but also by a decrease in the amount of the sperm accumulated in the epididymides.…”
Section: Discussionmentioning
confidence: 99%